Pengaruh Literasi Keuangan dan Literasi Digital terhadap Perilaku Keuangan dengan Self-Efficacy sebagai Variabel Mediasi pada Masyarakat Kabupaten Sumbawa - Niken Meylianisapitri; Arya Zulfikar Akbar (LPPM Institut Pendidikan Nusantara Global, 2026)
The phenomenon of technological disruption in the financial sector post-pandemic has transformed the economic landscape of society, including in Sumbawa Regency. The ability to adapt, reflected in financial literacy and digital literacy, has become an absolute prerequisite for shaping healthy financial behavior. This study aims to comprehensively analyze the influence of financial literacy and digital literacy on financial behavior, positioning self-efficacy as a mediating variable that bridges the gap between knowledge and action. The independent variables in this research are financial literacy and digital literacy. Financial behavior serves as the dependent variable, and self-efficacy acts as the mediating variable. This study used 150 samples taken from the productive-age population in Sumbawa Regency using purposive sampling technique. The data obtained were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The results of the study stated that each variable of financial literacy, digital literacy, and self-efficacy had a significant positive effect on financial behavior. Financial literacy and digital literacy also have a significant positive effect on self-efficacy. The self-efficacy variable as a parameter states that it partially mediates the effect of financial literacy on financial behavior, while the relationship between digital literacy and financial behavior is fully mediated by self-efficacy. The implications of this study emphasize the need for a holistic approach that not only transfers technical knowledge but also builds the self-confidence (self-efficacy) of the Sumbawa community in facing the digital economic ecosystem. A key theoretical contribution of this study is the explicit identification of the nature of self-efficacy mediation: it functions as a partial mediator between financial literacy and financial behavior, and as a full mediator between digital literacy and financial behavior, confirming that digital skills alone cannot drive healthy financial behavior without the psychological confidence provided by self-efficacy.